The Ecosystem of Competitive Employment for University Graduates with Autism. Issue 5 (3rd September 2022) - Vincent, Jonathan; Fabri, Marc
ABSTRACT: There is a growing population of young people with autism entering higher education and successfully completing qualifications, however, their postgraduate outcomes are often some of the poorest. This study responds to the gap in research regarding the transition out of higher education and into the labour market for this group. It outlines a two-phase qualitative research design to examine barriers and pathways to competitive employment for graduates with autism. Findings report the heterogenous experience of autism, the importance of natural supports such as family, universities, or supported employment for success, and the impact of attitudes regarding autism and inclusive practice expressed by employers and wider society. The study further analyses how people, practices and policies often interact contingently to open up or close down opportunities for graduates with autism within the ecosystem of competitive employment.